2021
DOI: 10.1038/s41598-021-95226-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the injury severity score and the probability of survival in patients who fell from height

Abstract: In Japan, falls from height result in the second highest trauma mortality rate after traffic motor vehicle collisions and the highest trauma-related mortality rate amongst young people. We aimed to identify factors that worsen injury severity and lower survival probability of patients who fell from height and to contribute to the improvement of their prehospital and in-hospital care. This retrospective analysis retrieved hospital records of 179 patients aged ≥ 15 years who were transported to our hospital afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…We confirmed that fall height, age, and suicidal intent were major determinants of death. This is consistent with the results of previous studies on the determinants of death in fall patients [33,34]. Fall height is a major factor that influences vertical deceleration injury patterns, with studies suggesting 6 or 7.5 m as the height of a fatal fall [35][36][37][38].…”
Section: Author Contributionssupporting
confidence: 91%
“…We confirmed that fall height, age, and suicidal intent were major determinants of death. This is consistent with the results of previous studies on the determinants of death in fall patients [33,34]. Fall height is a major factor that influences vertical deceleration injury patterns, with studies suggesting 6 or 7.5 m as the height of a fatal fall [35][36][37][38].…”
Section: Author Contributionssupporting
confidence: 91%
“…Therefore, if patients who have fallen from a height and injured their upper face are transported to a hospital at night, maxillofacial surgeons should suspect the occurrence of maxillofacial fractures. Generally, the height of the fall determines the kinetic energy transmitted to the patient, while the landing position and impact location determine the pattern and severity of the injury 22,26,27 . In the present study, although significant differences were found for impact location (i.e., between indoors and outdoors), when the fracture and non‐fracture groups were compared, this factor was not selected as significant after logistic regression analysis.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies have determined that factors that affect the mortality of patients who have fallen from a height include the fall height, impact surface properties, alcohol consumption, psychiatric medication use, suicide attempts, and body position at the time of surface impact. 22,23 Additionally, significant factors affecting the occurrence of maxillofacial injuries in patients who have fallen have been determined to be age (especially >60 years) and lack of formal education. 6 In the present case series, the mandibular fracture was the most common type of fracture, accounting for 79.7% (47/59) of all fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the distribution of therapeutic and diagnostic tactics in successive stages with the allocation of resuscitation and diagnostic, resuscitation and post-shock stages was first provided by P. M. Zamyatin et al (2006) [15]. The probability of survival of the wounded and injured largely depends on the measures taken at different stages of rescue and medical care [16,17]:…”
Section: Introductionmentioning
confidence: 99%